Modelling respiration of packaged fresh-cut "Rocha" pear as affected by oxygen - Gomes, M. Helena (2010)
Respiration rates were measured in fresh-cut ‘Rocha’ pear (Pyrus communis L.) stored at four temperatures (0, 5, 10 and 15 C) and with oxygen partial pressures ranging from 0 to 18 kPa. Respiratory quotient and ethanol production were used to determine the fermentation threshold. The oxygen concentration effect on the respiration rate was accurately described using Michaelis–Menten kinetics, without noncompetitive inhibition by CO2, and the effect of temperature on the respiration rate was well modelled by exponential functions. The oxygen level at which respiration was half its maximum (apparent Km;O2 ) was similar to or only slightly greater than the fermentation threshold. The narrow range of oxygen between Km;O2 and the fermentation threshold, suggests that modified atmosphere packaging technology has a limited applicability toward extension of the shelf-life of fresh-cut ‘Rocha’ pear.